A semiquantitative study of the optimal whole-body imaging time after 131I therapy for differentiated thyroid cancer - Liu, Shuang; Zuo, Rui; Yang, Tianyu; Pang, Hua; Wang, Zhengjie (Frontiers in Endocrinology, 2022)
Objective We compared the efficacy of post-therapy whole-body scintigraphy (Tx-WBS) in terms of detecting lesions in patients with differentiated thyroid cancer (DTC) on days 3, 7, and 10 after 131I treatment, and we determined the optimal imaging time. Methods Clinical data from 161 DTC patients treated with 131I were collected. All underwent Tx-WBS on day 3 after 131I treatment, 98 patients underwent day 7 imaging and 63 patients underwent day 10 imaging. And the thyroid bed uptake was visually graded. The radioactivity ratios of the thyroid bed, neck lymph nodes, lungs, and liver (to the background) were calculated to allow a semiquantitative analysis. Results Visual analysis showed that delayed imaging revealed more lymph node and lung radioactivity, early imaging showed more residual thyroid tissue, and significant differences in uptake were apparent on days 3, 7, and 10 (P < 0.001). Semiquantitative analysis revealed significant differences in the target-to-background ratios of the residual thyroid bed, lungs, and liver on days 3, 7, and 10. On these days, the imaging sensitivities in terms of detecting metastatic lymph nodes were 29.58%, 39.02%, and 19.35%, and the specificities were 75.56%, 75.86%, and 75% (P = 0.465, 0.154, and 0.763, respectively). In terms of lung metastasis detection, the sensitivities were 29.58%, 38.46%, and 13.33% respectively, and the specificities were 98.33%, 100%, and 95.83% (P < 0.001, < 0.001, and < 0.238). Conclusion More residual thyroid tissue can be detected by imaging on day 3; imaging on day 7 more effectively detects lung metastases than does imaging on day 3 or 10.